Geographical Indications as a Local Development and Differentiation Strategy Tool: The Case of Poland - Ciarko, Marta; Poszwa, Greta; Caner Timur, Mustafa (<center>Conference Proceedings Determinants Of Regional Development</center>; No 3 (2022): Conference Proceedings - IX International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/03/010, 2022)
After the industrial revolution, and especially in the last hundred years, the increase in the number of factories helped to make standardized mass productions in many areas and to experience production abundance. Presently, this situation, which allows individuals to obtain many products, especially food materials, quickly and cheaply, is considered as a positive situation in terms of economy and society. Today, it is expressed by some circles that standardized mass productions have some disadvantages, but also great advantages. Some of these can be listed as the concentration of production at certain points of the country, the danger of chemicals used in production to health and the environment, ignoring the ancient techniques adopted in the production process for centuries and leading to a deterioration in justice of income distribution. An important concept that stands out at the point of eliminating all these counted and uncounted negative externalities is geographical indications. These signs, which establish a link between the characteristic features of the products and their geographical area, have recently increased their popularity in many countries, especially under the leadership of countries such as France and Italy. From this point of view, this study aimed to examine the geographical indication products of Poland, which is a member of the European Union and whose historical ties are quite old, in the context of the importance and its effect on local development. The data to be used in the study is obtained from national institutions and the European Union commission. The findings show that Poland, which has a long history of culture and many traditional products, underutilizes its potential in the area of geographical indicators.